Response of heterogeneous vegetation to aerosol radiative forcing over a northeast Indian station. (15th January 2018) - Latha, R.; Vinayak, B.; Murthy, B.S.
Abstract: Importance of atmospheric aerosols through direct and indirect effects on hydrological cycle is highlighted through multiple studies. This study tries to find how much the aerosols can affect evapo-transpiration (ET), a key component of the hydrological cycle over high NDVI (normalized difference vegetation index)/dense canopy, over Dibrugarh, known for vast tea plantation. The radiative effects of aerosols are calculated using satellite (Terra-MODIS) and reanalysis data on daily and monthly scales. Aerosol optical depth (AOD) obtained from satellite and ground observations compares well. Aerosol radiative forcing (ARF), calculated using MERRA data sets of 'clean-clear radiation' and 'clear-radiation' at the surface, shows a lower forcing efficiency, 35 Wm −zs, that is about half of that of ground observations. As vegetation controls ET over high NDVI area to the maximum and that gets modified through ARF, a regression equation is fitted between ET, AOD and NDVI for this station as ET = 0.25 + (−84.27) × AOD + (131.51) × NDVI that explains 82% of 'daily' ET variation using easily available satellite data. ET is found to follow net radiation closely and the direct relation between soil moisture and ET is weak on daily scale over this station as it may be acting through NDVI. Highlights: Effect of ARF on surface evapo-transpiration (ET) is estimated from satellite data. Formula of ET derived as a function of NDVI and AOD. NDVI and AOD together accounts for 82% of observed ET. Reduction in ET is higher for denser canopies for a given ARF.